Whey Protein Isolate-Supplemented Beverage, Fermented by Lactobacillus casei BL23 and Propionibacterium freudenreichii 138, in the Prevention of Mucositis in Mice - Cordeiro, Bárbara F.; Oliveira, Emiliano R.; da Silva, Sara H.; Savassi, Bruna M.; Acurcio, Leonardo B.; Lemos, Luisa; Alves, Juliana de L.; Carvalho Assis, Helder; Vieira, Angélica T.; Faria, Ana M. C.; Ferreira, Enio; Le Loir, Yves; et al. (Frontiers in Microbiology, 2018)
Mucositis is a clinically important gastrointestinal inflammatory infirmity, generated by antineoplastic drugs cytotoxic effects.